Correlation between Intraoperative Ossicular Status and Conductive Hearing Loss Degree among Chronic Suppurative Otitis Media Patients in Dr Mohammad Hoesin General Hospital Palembang - Rizandiny; Ahmad Hifni; Erial Bahar; Abla Ghanie (HM Publisher, 2021)
Background: Chronic suppurative otitis media (CSOM) is a chronic inflammation of the mucosa and periosteum of the middle ear and mastoid cavity that defined as a perforated tympanic membrane with persistent drainage for more than 2 months. Preoperative hearing threshold and air bone gap (ABG) assessment are expected to predict the ossicular status which can only be ascertained intraoperatively. This study aimed to determine the correlation between intra-operative ossicular status and the degree of conductive hearing loss assessed based on the hearing threshold and average ABG among CSOM patients in RSUP Dr. Mohammad Hoesin Palembang. Methods: Observational research using a cross sectional design. The data were collected using medical record on 64 subjects with a diagnosis of CSOM who underwent mastoidectomy surgery at Dr. Mohammad Hoesin Hospital Palembang for the period of March 2019 to June 2021. Results: From 64 samples conducted in the study, the average ossicular status score in CSOM patients was 1.84 ± 1.48, with the highest group scoring 0 being the malleus incus and intact stapes as many as 21 patients (31.3%). There was a strong positive correlation between hearing threshold scores and intra-operative ossicular status scores (p<0.005, R=0.5) and there was a strong positive correlation between ABG scores and intra-operative ossicular status scores (p <0.005, R=0.6). From the linear regression test, the most influential in predicting intra-operative ossicular status scores were gender, hearing threshold value, ABG value, and the presence of cholesteatoma Conclusions: There is a significant relationship between intra-operative ossicular status and the degree of conductive hearing loss in CSOM patients.